Work-related Skin Disease Symptoms in Tofu Makers in Cipayung District - Mirta Dwi Rahmah Rusdy; Cut Alia Keumala Muda (Universitas Airlangga, 2023)
Introduction: One of the risks that may come from exposure to chemicals, physics, and biological agents in the interaction of processes in industrial activities, particularly in the business of making tofu in the tofu maker's environment, is a work-related skin disease. The number of years of employment, chemical exposure and the time spent each day, hand-washing routines, and the use of personal protective equipment while at work are additional risk factors known to influence the frequency of occupational skin disorders. This study seeks to obtain information about the symptoms and some risk factors of work-related skin diseases in tofu makers in Jalan Raya X, Cipayung District. Methods: The analytical cross-sectional design with a chi-square test was carried out with 50 tofu makers as the total research sample. Measurements were made using the modified Nordic Occupational Skin Questionnaire (NOSQ-2002)/LONG. Results: The study found that 46% (23 people) of tofu makers did experience symptoms of work-related skin diseases. As many as 84% (42 people) of tofu makers with a working period of more than 3 years, and as many as 96% (50 people) had exposure 3 hours per day. As many as 62% (31 people) had bad hand-washing habits, and 96% (48 people) did not fully use personal protective equipment. Conclusion: Improvement of supporting facilities and infrastructures in the production area, such as air circulation systems, modification of machinery and equipment, setting working hours, and providing proper cleaning facilities will increase the health status of workers.